1993
DOI: 10.1123/jsep.15.2.119
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Sport Commitment Model Using Structural Equation Modeling

Abstract: This article presents the results of a structural equation modeling analysis of the Sport Commitment Model. This model proposes that commitment is determined by sport enjoyment, involvement alternatives, personal investments, social constraints, and involvement opportunities. Preliminary analyses demonstrated that the model was applicable to both younger (< 12 years old) and older (> 13 years old) athletes, to males and females, and to three different team sports. Structural equation modeling results dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
59
1
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 0 publications
7
59
1
7
Order By: Relevance
“…Previous research has reported a relationship between athletes' satisfaction with their coach and coaches' overall coaching efficacy . In addition, athletes' satisfaction has been linked to their perceptions that their coach is competent in motivating them and influencing their psychological skills and states .A construct conceptually similar to satisfaction is sport enjoyment (Scanlan, Carpenter, Scanlan, Simons, & Lobel, 1993), which involves a positive emotional response to a sport experience that may include feelings such as pleasure, liking, and fun . The coaching efficacy model suggests that increased levels of coaching efficacy should result in higher levels of athlete satisfaction .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has reported a relationship between athletes' satisfaction with their coach and coaches' overall coaching efficacy . In addition, athletes' satisfaction has been linked to their perceptions that their coach is competent in motivating them and influencing their psychological skills and states .A construct conceptually similar to satisfaction is sport enjoyment (Scanlan, Carpenter, Scanlan, Simons, & Lobel, 1993), which involves a positive emotional response to a sport experience that may include feelings such as pleasure, liking, and fun . The coaching efficacy model suggests that increased levels of coaching efficacy should result in higher levels of athlete satisfaction .…”
mentioning
confidence: 99%
“…A construct conceptually similar to satisfaction is sport enjoyment (Scanlan, Carpenter, Scanlan, Simons, & Lobel, 1993), which involves a positive emotional response to a sport experience that may include feelings such as pleasure, liking, and fun . The coaching efficacy model suggests that increased levels of coaching efficacy should result in higher levels of athlete satisfaction .…”
mentioning
confidence: 99%
“…Results indicated that sport enjoyment and personal investments were the most important determinants, accounting for 58% of the variance in sport commitment. Carpenter et al (1993) examined the same model on a group of 1342 youth athletes from the sports of football, soccer, and volleyball using structural equation modeling.…”
Section: Initial Results Of the Sport Commitment Modelmentioning
confidence: 99%
“…This model is promising since initial testing with youth-sport athletes has supported the proposed relationships in the model (Carpenter, Scanlan, Simons, & Lobel, 1993;Scanlan & Carp::1!a et al, 1993;.…”
mentioning
confidence: 92%
“…Scale: SCS Scanlan et al, 1993a;Scanlan et al, 1993bCarpenter et al, 1993Casper and Andrew, 2008;Weiss et al, 2001 He andLin, 2009;Ma et al, 2008Scanlan et al 1993aScanlan et al 1993bScanlan et al 1993aScanlan et al 1993b How dedicated are you to playing in (program)? ", …”
mentioning
confidence: 99%